2019
DOI: 10.1111/1751-2980.12708
|View full text |Cite
|
Sign up to set email alerts
|

Relapse patterns and predictors of IgG4‐related diseases involved with autoimmune pancreatitis: A single‐center retrospective study of 115 patients

Abstract: Objective Autoimmune pancreatitis is an autoimmune disorder accompanied by clinicopathological manifestations that have been established as immunoglobulin (IgG)4‐related diseases (IgG4‐RD). Other IgG4‐RD are often involved with autoimmune pancreatitis. They sometimes relapse despite a favorable response to steroid therapy. This study aimed to clarify the patterns and risk factors for extrapancreatic relapse. Methods We reviewed the data of 115 patients diagnosed with definite autoimmune pancreatitis type 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…As mentioned above, relapse occurs in 24-52% of type 1 AIP cases [22,29,[72][73][74][79][80][81][136][137][138][139][140][141][142][143][144] and 0-27% of type 2 AIP cases [21,73,78] after cessation of corticosteroid treatment or dose tapering of corticosteroids. Identification of characteristics or risk factors for relapse is critical, as unnecessary steroid treatment in patients in whom recurrence is unlikely should be avoided.…”
Section: Recurrence Of Aip and Factors Associated With Recurrencementioning
confidence: 91%
See 1 more Smart Citation
“…As mentioned above, relapse occurs in 24-52% of type 1 AIP cases [22,29,[72][73][74][79][80][81][136][137][138][139][140][141][142][143][144] and 0-27% of type 2 AIP cases [21,73,78] after cessation of corticosteroid treatment or dose tapering of corticosteroids. Identification of characteristics or risk factors for relapse is critical, as unnecessary steroid treatment in patients in whom recurrence is unlikely should be avoided.…”
Section: Recurrence Of Aip and Factors Associated With Recurrencementioning
confidence: 91%
“…To date, several factors for predicting AIP relapse have been reported. These include a high level of serum IgG4 [22,79]; extrapancreatic lesions [78,80,136,137], especially proximal bile duct stenosis [73,136,138]; retroperitoneal fibrosis [139]; dacryoadenitis/sialadenitis [140]; jaundice [141]; discontinuation of steroid therapy [138,142,143]; a small reduction in the level of serum sIgG4 3-4 months after steroid initiation [80,81]; and a low level of pancreatic shrinkage following steroid treatment [144]. Maintenance corticosteroid therapy, with or without steroid-sparing agents, is recommended for type 1 AIP patients with factors predictive of relapse, although the therapeutic period is unclear.…”
Section: Recurrence Of Aip and Factors Associated With Recurrencementioning
confidence: 99%
“…There are a number of extrapancreatic manifestations correlated with IgG4 level [ 39 ]. Additionally, different organs seem to be involved based on the extent of IgG4 elevation [ 44 , 61 ]. The study by Ishikawa et al [ 42 ] revealed that all patients with AIP with kidney involvement displayed elevated IgG4, of whom 81% ( n = 17) had IgG4 higher than twice the ULN.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Ishikawa et al [ 42 ] revealed that all patients with AIP with kidney involvement displayed elevated IgG4, of whom 81% ( n = 17) had IgG4 higher than twice the ULN. Retroperitoneal fibrosis and lacrimal and salivary gland involvement are also accompanied by high IgG4 levels in patients with AIP [ 32 , 61 , 106 ]. Studies that investigate the relationship between IgG4 and the extension of extrapancreatic lesions in AIP are presented in Supplemental Table S2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation